INCLUSIVE ISLAMIC EDUCATION LEARNING IN THE TIME OF COVID-19 IN THE SD ISTANA HATI BINJAI - Fadhilah Juliandari; Munawir Pasaribu (Proceeding International Seminar of Islamic Studies, 2021)
Inclusive education is an education that receives a wide range of character and background of students to learn together in a learning climate. In the islamic view, education is a duty both to understand the islamic obligation and to build culture. The problem in this study is how inclusive education in the view of Islam and learning during covid-19 in Sd Istana Hati Binjai. The purpose of this study is to describe inclusive sducation in the islamic view at Sd Istana Hati Binjai. The benefits of this research are expected to supplement the authors' insights and insights on inclusive education from the islamic perspective in Sd Istana Hati Binjai. It’s a qualitative study. The subject of this study is a special-needs child Sd Istana Hati Binjai. Data collection is the process of finding data by way of obsevation, interview and documentary. Keywords: Inclusive Islamic Education, Special Needs Children, In The Covid-19 Era